Sosialisasi Potensi Bisnis Ikan Nila (Oreochromis niloticus) di Desa Nagrak, Kabupaten Cisaat, Sukabumi - Ima Kusumanti; Amalia Putri Firdausi; Dian Eka Ramadhani; Cecilia Eny Indriastuti (Agrokreatif: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2023)
Tilapia cultivation in Nagrak Village has been practiced for a long time as one of the community's sources of income. The aquaculture business is still carried out traditionally such as the use of ground ponds, feeding management that relies on natural feed, packaging that is not in accordance with standards, and fish marketing that only uses the direct selling technique (word of mouth). The obstacles faced by partners are limited knowledge on utilizing the potential of tilapia cultivation and processing, as well as the lack of planning and strategies of product marketing. This community service activity aims to provide insight into the potential for tilapia business development, introduce processed small tilapia fish called crispy baby fish as a healthy snack with economic value, and explain the description of business analysis, good packaging techniques, and online marketing. This activity was carried out with a socialization method or presentation of material to the Family Welfare Empowerment (PKK) group of 35 people. The material presented were introduction to tilapia farming, the business potential of crispy tilapia snacks, an overview of business analysis, and online marketing strategies. The conclusion obtained from community service activities in Nagrak Village is needed for training activities to increase community knowledge and skills on developing the potential of the tilapia business.